FORMING THE ABILITY TO USE THE DICTIONARY IN THE PROCESS OF ONLINE EDUCATION - Usmanova Shokhsanam Avazovna shoxsanam.shaxobova@gmail.com English teacher at academic lyceum "International House Tashkent" ESP teacher at MGIMO, Tashkent, Uzbekistan (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
: Learning vocabulary is a basic constituent of learning a language. Because of the importance of vocabulary to the four macro skills as well as to our study and life, much attention has been paid and many studies have been conducted to investigate effective dictionary learning strategies. Solutions to the problems and suggestions to improve the process of teaching and learning vocabulary were then presented, followed by implications for further research into effective vocabulary learning and dictionary teaching strategies in online teaching English. Key Terms – vocabulary, dictionary skill, taxonomy, strategy, dictionary learning strategies, using notebooks, lexical piece.